Does Gross Regional Domestic Product (GRDP) Affect Poverty in South Sulawesi? Two-Stage Least Squares (2SLS) Approach - Abjinda Putra Asmara; Muh. Rasbi; Ishak Ishak; Fasiha Fasiha; Muhammad Nur Alam Muhajir; Muh. Abdi Imam (Universitas Negeri Malang, 2025)
This research aims to determine the simultaneous relationship between poverty and PDRB variables in South Sulawesi. This type of research is quantitative which focuses on revealing simultaneous relationships between variables. The population is Poverty and PDRB data for districts/cities in South Sulawesi Province in 2020. The sample used is a saturated sample of 24 districts/cities sourced from the central statistics agency. Next, this research data was analyzed using the Two Stage Least Square (2SLS) method. The results of this research show that the poverty variable has a significant effect on PDRB at a significance level of 5%. Meanwhile, the PDRB variable has a significant effect on poverty at a significance level of 5%. So it can be concluded that there is a simultaneous relationship between PDRB and Poverty at a significance level of 5%. Control variables namely Income, Education and Expenditure have no influence on poverty. Control variables Population, PAD and HDI have a significant influence on poverty. The suggestion in this research is that regional governments, especially the province of South Sulawesi, should pay more attention to the equal distribution of income in each region to increase PDRB and also pay attention to other factors such as population, local original income and the Human Development Index (HDI).